Digital state-feedback control of an interleaved DC–DC boost converter with bifurcation analysis. (April 2018) - Gkizas, G.; Yfoulis, C.; Amanatidis, C.; Stergiopoulos, F.; Giaouris, D.; Ziogou, C.; Voutetakis, S.; Papadopoulou, S.
Abstract: This paper evaluates several state-feedback control design methods for a multi-phase interleaved DC–DC boost converter with an arbitrary number of legs. The advantages of state-feedback control laws are numerous since they do not burden the system with the introduction of further zeros or poles that may lead to poorer performance as far as overshoot and disturbance rejection is concerned. Both static and dynamic full state-feedback control laws are designed based on the converter's averaged model. Building on previous work, this paper introduces significant extensions on the investigation of several undesirable bifurcation phenomena. In the case of static state-feedback it is shown that interleaving can give rise to more severe bifurcation phenomena, as the number of phases is increased, leading to multiple equilibria. As a remedy, a bifurcation analysis procedure is proposed that can predict the generation of multiple equilibria. The novelty of this paper is that this analysis can be integrated into the control design so that multiple equilibria can be completely avoided or ruled out of the operating region of interest. The proposed control laws are digitally implemented and validated in a 2-leg case study using both simulation and experimentation.